Pengaruh Harga Dan Persepsi Konsumen Terhadap Keputusan Pembelian Produk Pada E-commerce Shopee Di Kecamatan Medan Tembung - Maduma, Novita Tiur; Manalu, Darma; Simangunsong, Ridhon NB. (Research and Community Service UNIVERSITAS KALBIS, 2025)
The rapid progress of internet has had a positive impact on the business world. One of the sectors most positively affected is marketplace and e-commerce. The high use of e-commerce and marketplaces in Indonesia is triggered by changes in people's habits, who now prefer convenience and speed. This research aims to find out how much influence price and consumer perception have on Shopee E-commerce purchasing decisions in Medan Tembung District. The data analysis method used is an instrument test consisting of validity and reliability tests, classic assumption tests consisting of normality tests, heterosdecadasticity tests, multiple linear regression analysis tests and hypothesis tests consisting of t-tests and coefficient of determination tests (R2). Based on hypothesis testing with the t test, the value of tcount is 10.256 > ttable, which is 1.986 and the significant value of the Price variable is 0.000 < 0.05. It can be concluded that price has a positive and significant effect on product purchasing decisions at Shopee e-commerce in Medan Tembung District.